PRO-KIND consensus protocol for classification, monitoring, and therapy in pediatric rheumatology: persistent oligoarticular juvenile idiopathic arthritis - Peitz, Joachim; Horneff, Gerd; Raab, Anna; Winowski, Hanna; Hansmann, Sandra; Tenbrock, Klaus (Frontiers in Pediatrics, 2026)
Protocols concerning classification, monitoring and treatment were developed for the oligoarticular form of juvenile idiopathic arthritis (JIA) as part of a consensus process. The aim was to establish standardized, evidence-based protocols for managing persistent oligoarticular JIA. The group of authors initially formulated 23 statements and circulated them in an online survey to medical members of the Society for Paediatric and Adolescent Rheumatology (GKJR). A total of 80 of the 124 paediatric and adolescent rheumatologists took part in the survey, which corresponds to just under 65% of the paediatric and adolescent rheumatologists active at the time. In a final online meeting, comments from the survey were incorporated into the statements and then agreed upon by the group of authors. Finally, for newly occurring oligoarticular JIA, 20 statements and a summary consensus treatment protocol were developed to optimise the treatment of persistent oligoarticular JIA.